Co-Creation of Local Development and Effective Public Participation. Sozialer Zusammenhalt („Social Cohesion”) Programme in Berlin as an Example of Practice - Aldona Wiktorska-Święcka (Polish Political Science Yearbook, 2023)
Co-creation of public policy can be considered a democratic innovation, all the more so as this approach seems to secure the possibility of „redefining what is democracy”. Understood this way, it is a direct source of changes in urban governance systems. Hence, the essence of the considerations is reflection on co-creation as a principle regulating the current urban governance practices and public participation in Berlin. The subject of the analysis in the empirical part of the paper is the Sozialer Zusammenhang („Social Cohesion”) Programme implemented since 2020. The aim is to present the specificity accompanying co-creation with citizens and evaluate the solutions’ effectiveness. Particular attention is paid to the key issue of what institutional arrangements support co-creation in a specific local context, i.e., at the neighbourhood level, and to discuss to what extent they can be considered effective public participation.